Controlled register‐based study of road traffic accidents in 12,651 Finnish cancer patients during 2013–2019 - Marja‐Liisa Huuskonen; Tero Koistinen; Niina Sihvola; Inkeri Parkkari; Sanna Palovaara; Ville Kytö; Jussi Sipilä; Sirkku Jyrkkiö; Eetu Heervä (Cancer Medicine, 2023)
Abstract Background Little controlled evidence exists on road traffic accident (RTA) risk among patients diagnosed with cancer, while clinicians are often requested to comment their ability to drive. The aim of this study was to evaluate RTA risk in a population‐based cohort of cancer patients living in Southwest Finland. Patients All adult patients diagnosed with cancer in 2013–2019 were included. Acute appendectomy/cholecystectomy and actinic keratosis patients without cancer were selected from the same region as the control cohort. Participants were cross‐referenced to a national driving licence database, yielding 12,651 cancer and 6334 control patients with a valid licence. Due to marked differences in their clinical presentation, the cancer cohort was divided into nine cancers of interest (breast, prostate, colorectal, lung, melanoma, head & neck, primary brain tumours, gynaecological and haematological malignancies). The nationwide law‐regulated motor liability insurance registry was searched for all RTAs leading to injury with claims paid to not‐ or at‐fault participants. At‐fault drivers were verified based on sex and birth year. Results During a median follow‐up of 34 months, 167 persons were at‐fault drivers in RTAs leading to injury. Among the nine cancers of interest, RTA risk did not differ from the control cohort. Among cancer patients, multivariable regression suggested male sex and opioid use, but not advanced cancer stage or given systemic therapy, as the most influential risk factors for RTA. Conclusions Cancer diagnosis itself was not associated with increased RTA risk, but other associated symptoms, medications, comorbidities or specific cancer subgroups may.